From space to soil: Advancing crop mapping and ecosystem insights for smallholder agriculture in Kenya - Guo, Zhe; Hettiarachchi, Upeksha; Zhang, Wei (International Food Policy Research Institute, 2024)
Crop mapping—identifying what farmers are growing on their fields—is essential to agricultural and land use planning and management. It is used to generate yield estimates and crop acreage statistics, predict food prices and assess damages from disasters and also to evaluate ecosystem health—all functions essential for agricultural export nations such as Kenya.